2019
DOI: 10.1177/1545968319856897
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability of Cognitive-Motor Interference Assessments in Walking With Various Task Complexities in Persons With Multiple Sclerosis

Abstract: Background: Simultaneous execution of motor and cognitive tasks can result in worsened performance on one or both tasks, indicating cognitive motor interference (CMI). A growing amount of research on CMI in persons with Multiple Sclerosis (pwMS) is observed. However, psychometric properties of dual-task outcomes have been scarcely reported.Objective: To investigate the between-day test-retest reliability of the motor and cognitive dual-task costs (DTC) during multiple CMI test conditions with various task comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 59 publications
0
25
2
Order By: Relevance
“…Surprisingly, no improvements were found on patient-reported experiences of dual tasking in daily life as measured by the questionnaire. It might be that the effects found in the dual task measures were not big enough to be clinically relevant, as the changes in DTC motor in the present study were lower than the previously reported minimal detectable change of approximately 12% for the DTC motor [22]. Other explanations of the lack of improvement on the dual task questionnaire might be that the activities in daily life are still somehow different from the dual tasks used in the current study (e.g.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Surprisingly, no improvements were found on patient-reported experiences of dual tasking in daily life as measured by the questionnaire. It might be that the effects found in the dual task measures were not big enough to be clinically relevant, as the changes in DTC motor in the present study were lower than the previously reported minimal detectable change of approximately 12% for the DTC motor [22]. Other explanations of the lack of improvement on the dual task questionnaire might be that the activities in daily life are still somehow different from the dual tasks used in the current study (e.g.…”
Section: Discussioncontrasting
confidence: 83%
“…Other studies however did find a difference between DTT and single task training on cognitive dual task performance in Parkinson disease patients [39] and elderly subjects [12]. Although the cognitive tasks used in the present study are conventional in literature, the DTC cognitive recently demonstrated low reliability and learning effects in pwMS, perhaps explaining part of these results [22].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…A recent meta-analysis on CMI showed that walking speed changes due to DT can differentiate healthy participants from those with neurological deficit (Al-Yahya et al, 2011), supporting the clinical utility of DT outcomes to detect and measure disability, disease progression and intervention effectiveness. Although in its infancy with respect to other neurological conditions, DT literature in MS showed promising results, both as assessment and rehabilitative methods (Veldkamp et al, 2019;Veldkamp et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…For example, people with MS showed a greatly increased postural sway and a large decrement in variability of anteroposterior and mediolateral sway velocity while executing a simple arithmetic task during balance maintenance as compared with controls [14,15]. Similarly, they showed increased stride time and decreased walking speed during walking under several cognitive conditions (ie, talking) [16][17][18]. Recently, findings regarding cognitive-motor performances were reported during upper limb tasks [19].…”
Section: Introductionmentioning
confidence: 99%